FORMULASI DAN UJI STABILITAS FISIK SEDIAAN EMULSI MINYAK IKAN LEMURU (Sardinella lemuru) - Patihul Husni; Yasarah Hisprastin; Melinda Januarti (As-Syifaa Jurnal Farmasi, 2019)
Lemuru fish (Sardinella lemuru), a small type of pelagic fish, is often found in Indonesia. Lemuru fish oil contains high omega-3 which is benecficial for health. One effort that can be done to optimize the benefits of lemuru fish oil is formulated as an emulsion dosage form. The purpose of this study was to determine the formula and physical stability of the lemuru fish oil emulsion. The method in this study included preparation of emulsions with varian concentration of fish oil (F1: 5%, F2: 10%, and F3: 15%) using natural emulgators (gummi arabicum) and physical stability tests carried out at two temperature variations, 25oC and 40oC for 30 days. Physical stability tests included organoleptic, homogeneity, emulsion type, viscosity, pH, and the size of the average globule. The organoleptic test results showed that the three formulas showed phase separation at different time points at both the storage temperatures. The viscosity test results showed that the viscosity of the three formulas has decreased during the storage period. In the emulsion type test it was shown that all three formulas had an oil-in-water (O/W) emulsion type. The pH test results indicated fluctuations during the storage period. The average globul size test results showed that the F3 emulsion formula has a larger average globule size than F1 and F2. In conclusion, the most stable formula was F3 that containing 15% fish oil. F3 was stable for more than 21 days at 25oC and more than 14 days at 40oC.